The application of gene xpert for the diagnosis of mycobacterium tuberculosis and MDR TB in Kota region - Dinesh Verma; Rashmi Sharma; Anita E Chand; Anil Saxena (International Journal of Medical Research and Review, 2016)
Background: Improved diagnosis of tuberculosis is a global priority for tuberculosis control which requires early case-detection. MDR-TB poses formidable challenges due to the complex requirements for diagnosis and treatment and so enhancement in the capacity to diagnose MDR TB is required. The objective of the study is to assess the performance of GeneXpert MTB/RIF as an initial diagnostic tool for diagnosis of Mycobacterium tuberculosis and MDR TB in kota region.Methods: Total 330 patients of all age groups having either pulmonary or extrapulmonary tuberculosis were included in the study with study period from February 2016 to July 2016 and samples collected were subjected to Gene Xpert.Results: Mycobacterium tuberculosis was reported in 102(30.90%) cases by Gene Xpert and Rifampicin Resistance was detected in 23(22.54%) out of these 102 cases.Conclusion: The implementation of the Xpert MTB/RIF assay could dramatically improve the rapid diagnosis of tuberculosis, especially in cases with suspicion of MDR and smear negative TB.